APPENDIX APPENDIX 3D Direct PCR of Intact Bacteria (Colony PCR). Issue 1 (12th August 2016) - Woodman, Michael E.; Savage, Christina R.; Arnold, William K.; Stevenson, Brian
Abstract : This protocol describes an efficient method for screening intact bacteria for the presence of desired DNA sequences using the polymerase chain reaction (PCR). This method is commonly referred to as colony PCR. © 2016 by John Wiley & Sons, Inc.